British pronoun use, prescription, and processing linguistic and social influences affecting'They' and'He' - Paterson, Laura Louise; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study considers the use of they and he for generic reference in post-2000 written British English. The analysis is framed by a consideration of language-internal factors, such as syntactic agreement, and language-external factors, which include traditional grammatical prescriptivism and the language reforms resulting from second-wave feminism.
Keywords: Linguistics; Feminist theory; Sociolinguistics; Sociology; Sex (Psychology).; Gender expression; Gender identity; Linguistics; Sociolinguistics; Gender Studies; Feminism